Al-Qur’an dan Kearifan Lokal Masyarakat Jawa: Studi Living Qur’an Penggunaan Ayat Kursi dalam Tradisi Nyarang Hujan di Probolinggo - Abd. Basid; Siti Widiatus Sholihah (IAIN Bengkulu, 2023)
The Qur’an is a dialogue partner in solving various problems in people's lives and can present various traditions, as in the appreciation of the people of Sidomukti Subdistrict, Kraksaan District, Probolinggo Regency in using the Ayat Kursi in the rain charmer tradition. This research aims to discuss the phenomenon of the living Qur’an using the Ayat Kursi in the raining tradition in Sidomukti as a means of moving rain when carrying out a celebration event. The main problem in this paper is: that the endeavour to ask God for protection so that it is kept away from various disasters does not mean refusing rain. The formulation of the problem in this paper is: how is the use of Ayat Kursi against the raining tradition and the response of the Sidomukti people to this tradition? This study uses a qualitative-descriptive research type from observation and interview data, which is then analyzed using the library research method. The results of this study know that; 1) the use of Ayat Kursi in the tradition of rain charmer in Sidomukti is an effort to move the rain not to contain elements of polytheism or contrary to Islamic teachings because from the start of its implementation, only came from the elements of trust (worship) to Allah and tawasul to Rasulullah with incense media, and 2) the use of Ayat Kursi in the rain charmer tradition in Sidomukti is a form of a community initiative to move the rain when the event is in progress.